The Role of Supply Chain Management Practices on Competitive Advantage and Performance of Agroindustry SMEs - Soemadi, Rd Roro Anggraini; Nadeak, Multi; Novitasari, Dewiana (IJOSMAS, 2022)
Effective supply chain management (SCM) has become a potentially valuable way to secure competitive advantage and improve organizational performance because competition is no longer between organizations but between supply chains. This study examines the relationship between the influence of SCM practices on competitive advantage and organizational performance. The data for this study were collected from 165 employees in one of the MSMEs in the Agroindustry in Indonesia. Survey data were analyzed using partial least squares structural equation modeling (PLS-SEM). The results suggest that higher levels of SCM practices can lead to increased competitive advantage and improved organizational performance. Also, competitive advantage can have a direct positive impact on organizational performance. This study also confirms the mediating effect of competitive advantage on the relationship between SCM practices and organizational performance.